Insights into the adsorption and corrosion inhibition properties of newly synthesized diazinyl derivatives for mild steel in hydrochloric acid: synthesis, electrochemical, SRB biological resistivity and quantum chemical calculations. Issue 1 (22nd December 2022) - Bedair, Mahmoud A.; Elaryian, Hani M.; Gad, Ehab S.; Alshareef, Mubark; Bedair, Ahmed H.; Aboushahba, Rabab M.; Fouda, Abd El-Aziz S.
Abstract : Two azo derivatives (TODB) and (DODB) were synthesized and characterized as mild steel (MS) corrosion inhibitors in 1 M HCl. Electrochemical data suggest that TODB and DODB are excellent inhibitors. They show anti-bacterial effect against SRB. Abstract : Two azo derivatives, 4-((4-hydroxy-3-((4-oxo-2-thioxothiazolidin-5-ylidene)methyl)phenyl) diazinyl) benzenesulfonic acid (TODB) and 4-((3-((4, 4-dimethyl-2, 6-dioxocyclohexylidene) methyl)-4-hydroxyphenyl)diazinyl) benzenesulfonic acid (DODB) were synthesized and characterized using Fourier-transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance ( 1 H-NMR) and mass spectral studies. Gravimetric methods, potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS), electrochemical frequency modulation (EFM) techniques and inductive coupled plasma-optical emission spectroscopy were used to verify the above two compounds' ability to operate as mild steel (MS) corrosion inhibitors in 1 M HCl. Tafel data suggest that TODB and DODB have mixed-type characteristics, and EIS findings demonstrate that increasing their concentration not only alters the charge transfer ( R ct ) of mild steel from 6.88 Ω cm 2 to 112.9 Ω cm 2 but also changes the capacitance of the adsorbed double layer ( C dl ) from 225.36 to 348.36 μF cm −2 . At 7.5 × 10 −4 M concentration, the azo derivatives showed the highest corrosion inhibition of 94.9% and 93.6%. The inhibitory molecule adsorption on the metal substrate followed the Langmuir isotherm. The thermodynamic activation functions of the dissolution process were also calculated as a function of inhibitor concentration. UV-vis, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX) techniques were used to confirm the adsorption phenomenon. The quantum chemical parameters, inductively coupled plasma atomic emission spectroscopy (ICPE) measurements, and the anti-bacterial effect of these new derivatives against sulfate-reducing bacteria (SRB) were also investigated. Taken together, the acquired results demonstrate that these compounds can create an appropriate preventing surface and regulate the corrosion rate.